2017
DOI: 10.3390/ijms18020348
|View full text |Cite
|
Sign up to set email alerts
|

Perindopril Induces TSP-1 Expression in Hypertensive Patients with Endothelial Dysfunction in Chronic Treatment

Abstract: Thrombospondin-1 (TSP-1) is a potent endogenous inhibitor of both physiological and pathological angiogenesis, widely studied as a target in drug development for treating cancer. Several studies performed in the cardiovascular field on TSP-1 are contradictory, the role of TSP-1 in the physiopathology of cardiovascular disorders (CVDs) being, for the moment, incompletely understood and may be due to the presence of several domains in its structure which can stimulate many cellular receptors. It has been reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 51 publications
(70 reference statements)
1
17
1
2
Order By: Relevance
“…In vastus lateralis muscle samples from subjects with essential hypertension, TSP1 protein levels, as characterized by Western immunoblot, trended higher than those in controls but did not reach significance (62). In patients with hypertension, elevated plasma TSP1 was noted in association with decreased forearm-mediated vasodilation (18). However, in this study, TSP1 levels appeared elevated in controls compared to TSP1 levels reported in controls elsewhere (184), suggesting possible confounding by platelet activation.…”
Section: A Redox Signaling In Stem Cellscontrasting
confidence: 54%
“…In vastus lateralis muscle samples from subjects with essential hypertension, TSP1 protein levels, as characterized by Western immunoblot, trended higher than those in controls but did not reach significance (62). In patients with hypertension, elevated plasma TSP1 was noted in association with decreased forearm-mediated vasodilation (18). However, in this study, TSP1 levels appeared elevated in controls compared to TSP1 levels reported in controls elsewhere (184), suggesting possible confounding by platelet activation.…”
Section: A Redox Signaling In Stem Cellscontrasting
confidence: 54%
“…9 MiR-194 has been demonstrated to have an effect on suppressing tumor in a variety of cancers. 14,15 A study demonstrated that THBS1 is relevant to chronic ocular surface inflammation after refractive surgery. 13 THBS1, a pathological inhibitor of endogenous angiogenesis, is widely studied in the development of drug targets for the treatment of cancer and connected to several cellular functions.…”
Section: Introductionmentioning
confidence: 99%
“…The medication administered during hospitalization consisted of non-steroidal anti-inflammatory painkillers, according to the hospital protocols [7][8][9][10][11][12], with respect to any pre-existent conditions such as diabetes mellitus [13][14][15][16][17][18][19][20] or cardiovascular conditions such as arterial hypertension [21][22][23][24][25][26].…”
Section: Resultsmentioning
confidence: 99%